2016
DOI: 10.1073/pnas.1606320113
|View full text |Cite
|
Sign up to set email alerts
|

An advanced modeling study on the impacts and atmospheric implications of multiphase dimethyl sulfide chemistry

Abstract: Oceans dominate emissions of dimethyl sulfide (DMS), the major natural sulfur source. DMS is important for the formation of non-sea salt sulfate (nss-SO 4 2− ) aerosols and secondary particulate matter over oceans and thus, significantly influence global climate. The mechanism of DMS oxidation has accordingly been investigated in several different model studies in the past. However, these studies had restricted oxidation mechanisms that mostly underrepresented important aqueous-phase chemical processes. These … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
371
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 239 publications
(436 citation statements)
references
References 39 publications
31
371
0
Order By: Relevance
“…Also, NO3, NH4 and BC showed low mass 30 concentrations (median: 0.04µg m Model studies found that the DMS is mainly (84% globally) removed via the photo-oxidation by OH radical (Kloster et al, 2006). Also, the aqueous-phase oxidation of DMS is dominant by O3 during the cloud process, and yield significantly amount of MSA (Hoffmann et al, 2016). These findings support that the DMS oxidation is controlled by photochemical process and its products should show daytime maximum associated with the solar radiation.…”
Section: Marine Organic Aerosol (Moa)mentioning
confidence: 99%
“…Also, NO3, NH4 and BC showed low mass 30 concentrations (median: 0.04µg m Model studies found that the DMS is mainly (84% globally) removed via the photo-oxidation by OH radical (Kloster et al, 2006). Also, the aqueous-phase oxidation of DMS is dominant by O3 during the cloud process, and yield significantly amount of MSA (Hoffmann et al, 2016). These findings support that the DMS oxidation is controlled by photochemical process and its products should show daytime maximum associated with the solar radiation.…”
Section: Marine Organic Aerosol (Moa)mentioning
confidence: 99%
“…The size-resolved cloud microphysics of deliquesced particles and droplets including cloud droplet formation, evolution, and evaporation is considered using a 1-D sectional approach. Further microphysical features of SPACCIM are already described in Wolke et al (2005) and results owing to these processes are presented in Tilgner et al (2013), Rusumdar et al (2016), and Hoffmann et al (2016). The implemented multiphase chemical model applies a high-order implicit time integration scheme, which utilizes the specific sparse structure of the model equations (Wolke and Knoth, 2002).…”
Section: Box Model Spaccim (Original Code)mentioning
confidence: 99%
“…9), in contrast to their simultaneous emergence in the aftermath of LPS02 described in Piel et al (2006). Given that MS -should have been primarily formed by heterogeneous liquid phase chemistry prevalent in the marine boundary layer (Legrand et al, 2001;Bardouki et al, 2002;Hoffmann et al, 2016), the segregated MS -peak indicated a temporary and efficient advection of such air masses. In 5 addition a striking peak of the sea-salt tracer Na + appeared along with the MS -maximum (Supplementary Material, S.4), emphasizing the impact of marine boundary layer air masses during this part of LPS15.…”
Section: Ionic Composition Of Bulk-and Size Segregated Aerosolmentioning
confidence: 97%
“…13, starting point 100 m above Kohnen): Air masses during LPS15 Regarding the chemical composition of the aerosol during the final stage of LPS15, subsequent increasing nss-SO4 2-along with declining MS -concentrations indicated a minor importance of liquid phase chemistry (Hoffmann et al, 2016). We may 25 speculate that now intrusions of marine boundary layer into the so-called buffer layer which Russel et al (1998) assumed to extend from the turbulent marine boundary layer (400 m to 700 m) to a capping inversion (1400 m to 1900 m), were responsible for efficient advection of gaseous DMS photo oxidation products like SO2 and DMSO (Davis et al, 1998;Russel et al, 1998).…”
Section: Ionic Composition Of Bulk-and Size Segregated Aerosolmentioning
confidence: 99%